Sphenochoanal Polyp - Acharya, K; Pradhan, B; Thapa, NM; Khanal, S (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Key words: Sphenochoanal; choanal polyp; antrochoanal DOI: 10.3126/njenthns.v1i1.4734 Nepalese J ENT Head Neck Surg Vol.1 No.1 (2010) p.21-23